Regional Heterogeneity, the Rise of Public Debt and Monetary Policy in Post-Bubble Japan: Lessons for the EMU - Raphael Fischer; Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2016)
Both Japan and parts of the European Monetary Union have experienced boom and bust in stock and real estate markets, which have been followed by a lasting crisis. The paper analyses the role of a high degree of regional heterogeneity for public debt and monetary policy in the context of crisis. It is shown for Japan that the attempts to maintain regional cohesion via a regional transfer mechanism has contributed to the unprecedented rise in public debt and persistent monetary expansion. Econometric estimations show that in Japan regional redistribution of funds has ensured homogeneous living conditions across Japanese regions pre- and post-crisis. The side condition is monetary expansion. A similar effect could emerge in Europe, if the crisis persists.
Keywords: H12; H77; E52; 330; Japan; EMU; crisis; regional redistribution; monetary policy; public debt